2001
DOI: 10.1254/jjp.86.137
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Cerebrovascular Physiology and Pathophysiology

Abstract: ABSTRACT-Numerous studies have uncovered a wide variety of estrogen effects with apparent cardiovascular benefits, the most recognized ones being vasodilation, anti-atherogenesis, diminished post-ischemic inflammation and anti-oxidant effects. This article provides an overview of the influence of estrogen on the cerebral vasculature, under physiologic and pathophysiologic conditions, and covers both acute and chronic effects. The discussion is primarily focused on the vasodilatory and anti-inflammatory actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 174 publications
(155 reference statements)
1
22
0
Order By: Relevance
“…The increase in leukocyte adhesion in chronically estrogen-depleted females seen in the present and previous investigations appears to relate, at least in part, to a diminished cerebrovascular eNOS activity. However, it should be emphasized, as discussed in earlier reports, 1,2,6 that the influence of estrogen on cerebral leukocyte adhesion probably involves eNOS-independent actions as well. The documented repression of eNOS function likely relates to a downregulation of eNOS expression combined with an upregulation of the endogenous eNOS inhibitor CAV-1, since reducing leukocyte adhesion to levels seen in "estrogen-normal" females required a concomitant increase in eNOS and decrease in CAV-1 expression in cerebral venules.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The increase in leukocyte adhesion in chronically estrogen-depleted females seen in the present and previous investigations appears to relate, at least in part, to a diminished cerebrovascular eNOS activity. However, it should be emphasized, as discussed in earlier reports, 1,2,6 that the influence of estrogen on cerebral leukocyte adhesion probably involves eNOS-independent actions as well. The documented repression of eNOS function likely relates to a downregulation of eNOS expression combined with an upregulation of the endogenous eNOS inhibitor CAV-1, since reducing leukocyte adhesion to levels seen in "estrogen-normal" females required a concomitant increase in eNOS and decrease in CAV-1 expression in cerebral venules.…”
Section: Discussionmentioning
confidence: 84%
“…3,4 NO produced in the endothelium is well known for its antiadhesive properties. 5,6 Recently, in a preliminary study, we attempted to decrease leukocyte adhesion in ovariectomized (OVX) female rats via an estrogen-independent upregulation of brain eNOS expression. Thus, experiments using chronic treatment of the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor simvastatin were performed.…”
mentioning
confidence: 99%
“…This effect has been explained by the positive influence of endogenous estrogens on the availability of NO (16), the principal vasodilator in shearmediated vasodilation (31). Indeed, numerous studies have implicated estrogen as both a prostaglandin promoter and an antioxidant (2), protecting NO from degradation and facilitating increased vasomotion (17,29,39). However, it must be noted that in the present study we standardized study visits for women to coincide with days 1-7 of the menstrual cycle, when circulating estrogen is most likely to be lowest and most similar to concentrations measured in men (16).…”
Section: A Hormonal Milieu Effect On Flow-mediated Dilation?mentioning
confidence: 99%
“…Indeed, epidemiologic studies have revealed that atherosclerosis, hypertension, and peripheral vascular and coronary artery diseases occur with greater prevalence in men and in postmenopausal women compared with premenopausal women (4,23,26), while clinical assessments of endotheliumdependent peripheral artery vasomotion, flow-mediated vasodilation (FMD), in healthy populations suggest that vascular function is superior in premenopausal women compared with their postmenopausal counterparts and with men (27,40,52). En masse, these studies have implicated estrogen as both a prostaglandin promoter and an antioxidant, protecting nitric oxide (NO) from degradation and facilitating increased vasomotion (29,39). Thus current knowledge suggests that female sex hormones, such as estrogen, have positive vascular effects, whereas their absence could be related to vascular dysfunction and subsequent atherogenic disease states.…”
mentioning
confidence: 99%
“…More questions than answers were generated by the Women's Health Initiative study and combined with the fact that the general population lives longer, evaluating the protective mechanisms of E2 against brain injury continues to be the objective of many ongoing studies. Several excellent reviews on cellular/molecular mechanisms involved in E2's ability to modulate cerebrovascular function under normal and diseased states are recommended to the reader as they are not discussed in this review: [66,73,96,97,99,117,118].…”
Section: Androgens and Cerebrovascular Diseasementioning
confidence: 99%